PENGARUH PENGARUH KEBIJAKAN DIVIDEN MEMODERASI PROFITABILITAS, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2019-2022 - Cahya, Muhammad Alif Nur; Sari, Lita Permata; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2024)
Financial management is a process of managing and controlling finances in an organization or company, which includes planning, organizing, directing and controlling financial activities such as the acquisition and use of funds. The main objective of financial management is to maximize company value and ensure that financial resources are used efficiently and effectively. The aim of this research is to analyze and test the influence of dividend policy in moderating profitability, company size and leverage on company value in packaging and plastics sub-sector companies listed on the Indonesian Stock Exchange (IDX) in 2019-2022. The population in this study was 16 companies, which were then narrowed down based on criteria to become 8 companies. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Profitability has a positive but not significant effect on company value. Company size has a positive but not significant effect on company value. Leverage has a positive but not significant effect on company value. Dividend policy is unable to moderate the relationship between profitability and company value.